Garbo Laughs: Revolution and Melancholia in Lubitsch's Ninotchka - Jukić, Tatjana (2007)
Ernst Lubitsch’ s Ninotchka (1939)— a Hollywood comedy about various reinvestments of the communist revolution, advertised at the time as a film in which Garbo laughs— advertises in turn a position from which to review the scopes of specters, revolution and mourning, especially as they emerge in Jacques Derrida’ s Specters of Marx: The State of the Debt, the Work of Mourning and the New International (1994). From within a 1939 coming together of Garbo, comedy and communism in the so called Lubitsch touch, my presentation aims to reassess the chronology of Marxism implicit in Derrida’ s Specters and locate, in the Hollywood cinema, a time out of joint warping the more recent critical configurations of (post)communism.